Experimental hypovitaminosis A in rabbits - SRAVANTHI, A K; PARIHAR, N S; SHARMA, A K; SASTRY, V R B (The Indian Journal of Animal Sciences, 2013)
In the experimental studies on induced hypovitaminosis A in rabbits unthriftiness, weakness, alopecia and weight loss were noticed; and xerophthalmia and blindness were the main signs, Symptoms were marked in young animals in 68-80 days ,and in adult rabbits in 80-110 days of experimentation, Haematological studies revealed anaemia and leucopenia. Neutrophilic counts decreased while lymphocytic counts increased. Vitamin A content in the blood plasma of vitamin A deficient animals was remarkahly reduced from the initial pre-experimental mean values of 76.7Â±2,37)alpha g/100 ml to 9 alphag/100 ml in young group and to 16 pg/1 00 ml in adult rabbits. Similarly vitamin A in the liver at the end of experiment revealed low figures of 1 to 3 alphag/100 g in young and 1 to 8 pg/100 g in adult rabbits compared to average control values of l83,00Â±1 1.05 alphag/100 g.